(untitled) (Movimenta (ISSN 1984-4298), 2022)
Background: Palliative care is holistic care for individuals of any age and serious illness that leads to prolonged deterioration, disability or death. Isolated drug therapy does not serve the human totality, beyond to produce adverse effects. Thus, the choice of adjuvant approaches such as massage has become more frequent, however the evidence of the effectiveness of classical massage in the management of symptoms is uncertain. Purpose: The aim of present study is to verify the available evidence of the effects of classical massage on terminally ill patients. Data Sources: This is a systematic review, carried out based on the PRISMA recommendations and developed with studies registered in the PubMed, Cochrane Library and PEDro databases, with search until January 2021. Results: Only 6 were selected for qualitative analysis. The main findings indicate that the effects of massage provide balance of mood, reduction of anxiety and pain when used as a resource in palliative care but limited to the short term. Conclusions: Massage in patients in palliative care reduce anxiety and pain in the short term and promote balance of mood. When associated with aromatherapy, it promotes decrease in anxiety and physical symptoms and increase in quality of life, and when associated with meditation, it improves quality of life and interpersonal relationships.